Sosialisasi Kesehatan Mental pada Kelas VII di SMP Negeri 17 Surakarta - Desy Rosiana; Dhian Riskiana Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Adolescence is a transitional period full of emotional, physical, and biological changes. Although physical health is often the main focus of teenagers, mental health is a more important aspect to maintain. Balanced mental health can contribute to a person's happiness in life. However, in Indonesia, even though there is Law No. 18 of 2014 concerning Mental Health, mental health problems are still often ignored. Bullying is one of the factors that can damage teenagers' mental health. At SMP Negeri 17 Surakarta, bullying has become a problem that affects the mental well-being of students, both as perpetrators and victims. For this reason, community service with the theme